Euplocania cearaensis Silva-Neto, García Aldrete & Rafael, 2019 (Psocodea, ‘Psocoptera’, Ptiloneuridae): description of the female, update of the diagnosis and variation in the wing venation - Reategui, Natália S.; Silva-Neto, Alberto M.; Rafael, José A. (Entomological Communications, 2020)
The female of Euplocania cearaensis Silva-Neto, García Aldrete & Rafael, 2019 is described and illustrated, new records on variation in the fore and hind wings venation and an update of the diagnosis are provided. The material of this study where from two localities in the Parque Nacional de Ubajara, Ubajara, Ceará, Brazil.